Effects of inorganic arsenic species on the antioxidant enzyme system of the Amazon Sword Plant (Echinodorus amazonicus Rataj). (7th October 2022) - Şener, İdris; Yabanlı, Murat; Yozukmaz, Aykut
Abstract: This study aims to examine the effects of Arsenite (As +3 ) and Arsenate (As +5 ) on the aquatic macrophyte Amazon Sword Plant ( Echinodorus amazonicus Rataj). To this aim, different concentrations of As +3 and As +5 (0, 6, 18 and 54 μM) were analyzed. At the end of the trail, photosynthetic pigment contents, total protein amounts, the enzymatic antioxidants superoxide dismutase (SOD), peroxidase (POX) and catalase (CAT) activities and the amount of malondialdehyde (MDA) in the leaf samples of E. amazonicus were investigated. The antioxidant enzyme activities increased at low concentrations (32.13% for SOD, 185% for CAT and 201.5% for POX in the groups of 6 μM As +5 ), but decreased at high concentrations (64.98% for SOD, 21.64% for CAT and 21.29% for POX in the groups of 54 μM As +3 ). MDA increased in all the treatment groups. The highest MDA contents were observed as 96% for 54 μM As +3 and 71.50% for 54 μM As +5 . Photosynthetic pigment contents and the amount of protein were decreased with higher concentrations. The most significant decreases in protein content were 65% for 54 μM As +3 and 34.9% for 54 μM As +5 . As a result, the toxicity of As +3 was higher and the toxic effect increased at higher concentrations. HIGHLIGHTS: Oxidative stress caused by inorganic arsenic on aquatic plants was determined. At high concentrations of arsenic ions, both antioxidant enzyme activity and photosynthetic pigment contents were decreased. It was found that the As +3 ion is more toxic than the As +5 ion. The results of this study showed that plants will not survive if exposed to arsenic for a long period. Graphical Abstract